Surfactant-free self-assembly of reduced graphite oxide-MoO2 nanobelt composites used as electrode for lithium-ion batteries - Zhu, Y.; Xu, X.; Chen, G.; Zhong, Y.; Cai, R.; Li, L.; Shao, Zongping (Pergamon, 2016)
Graphene/metal oxide nanocomposites are promising electrode materials for lithium-ion batteries (LIBs), in which synergistic effects between the two components may benefit the overall capacity, rate capability and cycling stability. Here, we report a simple and easy scale-up method for the preparation of high-quality reduced graphite oxide-MoO2 (rGO-MoO2) nanobelt composites, which demonstrate attractive electrochemical performance as LIB anodes. MoO3 nanobelts are first prepared by a simple hydrothermal route and distributed homogeneously in water, and then graphite oxide (GO) is prepared by a modified Hummers method and introduced into the solution. Both materials slowly self-assemble to form GO-MoO3 nanocomposite in a surfactant-free manner. After thermal reduction, rGO-MoO2 nanobelt composites are obtained, as confirmed by FE-SEM and TEM. Using such composite as LIB electrodes, a reversible capacity of 754 mA h g-1 is obtained after 80 cycles at 0.2 A g-1, and the electrode also demonstrates superior rate capabilities. These results are comparable to or even higher than those of other reported graphene-MoO2 composites, which are fabricated in more complicated fashions, thus rendering the current product as highly promising electrode materials for practical use.